KEPEMIMPINAN KUNCI KEBERHASILAH KEPALA SEKOLAH - M. Idris (CV. ADIBA AISHA AMIRA, 2026)
School is an institution that has a complex and unique nature. It is complex because as an organization, it is bound by formal rules, has clear programs and targets, and has a leadership structure in its implementation. While the unique nature shows that the school as an organization has characteristics that are not possessed by other organizations. The characteristics that make the school have its own character are the teaching and learning process and character formation so that humans live in a cultured way. The principal as a leader has an active role and is always influential in all problems related to the needs of staff, teachers and students at school. There are five roles that must be carried out and mastered by a principal, namely the role as a formal official, manager, leader, educator, and staff. To support this role, the principal must have eight abilities, namely: Being able to work with others, being responsible and ready to be accountable, being able to face problems in limited time and resources. Thinking analytically and conceptually, acting as a mediator, acting like a politician, acting as a diplomat and being able to make difficult decisions.